Linking Childhood Cultural Health Capital Factors with Adult Health Literacy - Sasha A. Fleary (SLACK Incorporated, 2024)
Adult health outcomes are linked to childhood factors such as socioeconomic status via cultural health capital (CHC). Specifically, these factors shape opportunities for developing skills for navigating health environments via experience and the intergenerational transfer of health-related knowledge and skills. Health literacy (HL) is considered a part of and/or result of CHC. HL develops similarly to CHC via opportunities and experiences. Most research to date has ignored the effect of childhood factors on adult HL. The purpose of this study was to explore how childhood factors are related to adult HL. Data were collected from adults (N = 736, mean age = 40.65 years, standard deviation [SD] = 15.39; 52% female; 53.8% White, 31.3% Hispanic and Latino/a/e) in the United States using Qualtrics Panel. Multivariate ordinal and binary logistic regressions predicting HL (as measured by the Newest Vital Sign and Single-Item Literacy Scale) from childhood factors and accounting for demographic covariates were estimated. After accounting for covariates, such as the presence of an employed adult in a white-collar (odds ratio [OR] = 3.34) or blue-collar (OR = 3.68) occupation (versus unknown/not employed) increased the odds of being categorized as possible limited literacy and adequate literacy (versus limited literacy) as measured by the Newest Vital Sign. Similarly, having an employed adult during childhood who had a blue-collar occupation (vs. unknown/not employed) increased the odds of being categorized as adequate literacy (OR = 2.06) as measured by the Single-Item Literacy Scale. Because the adult's employment played a role in the child's adult HL after accounting for other factors and demographics, these findings support using a lifespan approach to assess and identify risk factors for lower HL. This study contributes to the growing body of evidence of how HL is interconnected with social determinants of health across the lifespan and the need to address HL skills in those with poor social determinants of health. [HLRP: Health Literacy Research and Practice. 2024;8(2):e79-e88.]